2013
DOI: 10.1021/ja311689k
|View full text |Cite
|
Sign up to set email alerts
|

Mn-Catalyzed Aromatic C–H Alkenylation with Terminal Alkynes

Abstract: The first manganese-catalyzed aromatic C-H alkenylation with terminal alkynes is described. The procedure features an operationally simple catalyst system containing commercially available MnBr(CO)(5) and dicyclohexylamine (Cy(2)NH). The reaction occurs readily in a highly chemo-, regio-, and stereoselective manner delivering anti-Markovnikov E-configured olefins in high yields. Experimental study and DFT calculations reveal that (1) the reaction is initiated by a C-H activation step via the cooperation of man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(156 citation statements)
references
References 71 publications
5
150
0
1
Order By: Relevance
“…22 DFT calculations further demonstrated that, through the cooperation of MnBr(CO) 5 and Cy 2 NH, the C-H bond cleavage only needed to overcome a barrier of 12.5 kcal/mol, which are in good line with the experimental results. We believed that the C-H activation proceeded via a base-assisted deprotonation mechanism, which was further confirmed by deuterium-labeling experiments.…”
Section: Scheme 14 Mn-catalyzed Aromatic C-h Alkenylation With Terminsupporting
confidence: 79%
See 2 more Smart Citations
“…22 DFT calculations further demonstrated that, through the cooperation of MnBr(CO) 5 and Cy 2 NH, the C-H bond cleavage only needed to overcome a barrier of 12.5 kcal/mol, which are in good line with the experimental results. We believed that the C-H activation proceeded via a base-assisted deprotonation mechanism, which was further confirmed by deuterium-labeling experiments.…”
Section: Scheme 14 Mn-catalyzed Aromatic C-h Alkenylation With Terminsupporting
confidence: 79%
“…Though manganese-mediated stoichiometric reactions of arenes bearing auxiliary groups with alkynes have been reported by Liebeskind, Nicholson, Woodgate, and others since 1989, 12-17 manganese-catalyzed aromatic C-H alkenylation with alkynes remained elusive before our work (Scheme 14). 22 We found that 2-phenylpyridines reacted smoothly with terminal alkynes affording E-alkenylated product 61 in the presence of catalytic amounts of MnBr(CO) 5 and dicyclohexylamine (Cy 2 NH). This reaction is noteworthy in the following aspects: First, the alkenylation process exhibited a high chemo-, regio-, and stereoselectivity with neither dialkenylated products nor Markovnikov adducts detected in the reactions, while only a small amount of Z-isomeric products were detected in some cases.…”
Section: Mn-catalyzed C-h Activation For C-c Bond Formationmentioning
confidence: 91%
See 1 more Smart Citation
“…In this reaction, delivering anti-Markovnikov E-coffingured olefins (43) in good yields (Scheme 20). [35] In 2014, Kakiuchi et alreported alkenylation reactions of 2-aryl pyridines with the alkenyl esters using Ru(cod)(cot) as a catalyst. [36] The reaction was performed on various 2-aryl pyridi < nes (3) and related aromatic compounds with a variety of alkenyl esters (44) including 1-or 2-monosubstituted and 1,2-or 2,2-disubsituted vinyl esters to obtain the alkenylated products (45) (Scheme 21).…”
Section: Alkenylation Of 2-aryl Pyridinesmentioning
confidence: 99%
“…[3] Among these catalysts, Mn-catalysts in CÀ H functionalization reactions have received momentum in recent days. [7] Later, several groups have independently employed terminal alkynes as well as internal alkynes as coupling partners with various substituted aromatics. [7] Later, several groups have independently employed terminal alkynes as well as internal alkynes as coupling partners with various substituted aromatics.…”
mentioning
confidence: 99%